Implementation smart charging technique using particle swarm optimization to achieve best performance charger - Indhana Sudiharto; Farid Dwi Murdianto; Lavia Isnani (Institute of Advanced Engineering and Science, 2023)
These days, there are an increasing number of electronic devices that use batteries as their energy source, often known as portable electronic devices. However, the battery may run out of energy and a recharging process is required to keep the electronic device functional. A charger that is in accordance with the battery specifications is required to complete the charging process. Incompatible chargers can overcharge batteries and shorten their lifetime. Since there are many different types of electronic devices, many different chargers are required, especially since most chargers on the market are static and can only be used with one kind of electronic device. This will increase the costs that customers must pay, especially those who have many types of electronic devices. As a result, this research will create a smart charger using the PSO algorithm that can be used to complete the charging process on all types of portable electronic devices. To test smart chargers, five different battery types from electronic devices with different specifications are used. From the test result, the smart charger can charge five different types of battery loads with various specifications with 100% accuracy at a speed that takes 50.4 seconds to reach a steady state.